2020
DOI: 10.7150/jca.45389
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D inhibits the proliferation of Oral Squamous Cell Carcinoma by suppressing lncRNA LUCAT1 through the MAPK pathway

Abstract: Background: Oral squamous cell carcinoma (OSCC) is the most common type of oral cancer worldwide. Recent studies have suggested that vitamin D (VitD) is associated with a reduced risk of many chronic illnesses, including cancer. However, the role of vitamin D in OSCC has rarely been reported. Materials and Methods: The effect of vitamin D and control treatment were examined by cell clone formation assay. Using RNA-seq, we globally identified VitD-regulated long noncoding RNAs (lncRNAs). The expression of LUCAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…↓ BRAF-activated long noncoding RNA (BANCR) luteolin thyroid carcinoma [182] long non-coding RNA epigallocatechin-3-gallate lung cancer [183] ↓ lnc RNA LINC00511 gastric cancer [184] ↓ lncRNAs H19 sulforaphane pancreatic ductal adenocarcinoma [185] ↓ lncRNA LUCAT1 vitamin D oral squamous cell carcinoma [186] ↓ lncRNA CCAT2 ovarian cancer [187] ↑ lncRNA MEG3 colorectal cancer [188]…”
Section: Mechanisms Bioactive Component Disorders Referencesmentioning
confidence: 99%
“…↓ BRAF-activated long noncoding RNA (BANCR) luteolin thyroid carcinoma [182] long non-coding RNA epigallocatechin-3-gallate lung cancer [183] ↓ lnc RNA LINC00511 gastric cancer [184] ↓ lncRNAs H19 sulforaphane pancreatic ductal adenocarcinoma [185] ↓ lncRNA LUCAT1 vitamin D oral squamous cell carcinoma [186] ↓ lncRNA CCAT2 ovarian cancer [187] ↑ lncRNA MEG3 colorectal cancer [188]…”
Section: Mechanisms Bioactive Component Disorders Referencesmentioning
confidence: 99%
“…Previous studies have focused on OSCC protein-coding genes (5,6). Recent studies have shown that lncRNA may serve an important role in the pathogenesis of OSCC (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the MAPK signaling pathway is involved in the development of OSCC, and TNFα regulates EMT through the MAPK signaling pathway to promote the invasion and metastasis of OSCC [57,58].…”
Section: Discussionmentioning
confidence: 99%